(untitled) (Colección, 2017)
Chilean migration to Patagonia in Argentina had special features since the overthrow of the constitutional government of Salvador Allende in the coup led by General Augusto Pinochet on September 11, 1973. This historic event began the exile of thousands of Chileans. The extent and permeability of the border turned Argentina into one of the best options for the most vulnerable sectors, especially those without protection and political contacts to organize their departure. The vulnerability of Chilean migrants arriving daily to the dioceses of Argentina in Patagonia motivated the organization of binational ecclesial meetings and pastoral activities specifically geared to them. This article examines the documents and publications issued after these binational meetings of bishops and pastoral agents of migration in the seventies, and intends to clarify the approach taken by the Catholic Church towards the new regional phenomenon, analyze the nature of their interventions and determine the features that took the relationship among the Church, the state and the society in the context of this specific problem.